Formation of readiness of future teachers to creative activity in school - Mussabekova, Gulnar; Asel Tasova, Batyrkhan Auyezov,; Gulim Kozhakhmetova., Zhaudir Sultanbekova, Zhanar Akhmetova, (Opción, 2019)
Research objective is to reveal the level of readiness for future teachers to creative activity at school and to provide its realization with the author's methods. The model and an author's methods of formation of readiness at future teachers to creative activity at school are developed. The practical value of work is that the developed model of readiness at future teachers to creative activity at school, the methods of consecutive work on formation of this readiness, the methods of diagnostics of readiness can be used in teaching practice of pedagogical higher education institutions, and also by teachers of comprehensive schools.